2016
DOI: 10.2217/cns-2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma in the elderly: treatment patterns and survival

Abstract: OS was maximized in elderly patients who were able to get some surgical resection and undergo combined radiation and chemotherapy. OS survival in some elderly patients may be improved by more extensive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
(33 reference statements)
1
22
0
Order By: Relevance
“…We found that patients over the age of 60 years were less likely to receive adjuvant therapies than younger patinets. Similar trends have been observed in glioblastoma patients, in which age was the most significant predictor of the type of treatment received, with elderly patients less likely to receive adjuvant RT and CT [36,37]. As expected, the survival outcomes for younger patients were significantly better than those for older patients (median OS: 14.5 vs. 8.2 months; p < 0.001).…”
Section: Discussionsupporting
confidence: 78%
“…We found that patients over the age of 60 years were less likely to receive adjuvant therapies than younger patinets. Similar trends have been observed in glioblastoma patients, in which age was the most significant predictor of the type of treatment received, with elderly patients less likely to receive adjuvant RT and CT [36,37]. As expected, the survival outcomes for younger patients were significantly better than those for older patients (median OS: 14.5 vs. 8.2 months; p < 0.001).…”
Section: Discussionsupporting
confidence: 78%
“…In our cohort, 56/123 (45.5%) showed an improved or unchanged postoperative KPSS with a median of 50%. Adjuvant treatment such as radiation therapy or chemotherapy is usually only offered to patients with a KPSS ≥ 70% [20,12]. Consequently, these patients are usually considered ineligible for adjuvant oncological treatment even after tumour resection.…”
Section: Discussionmentioning
confidence: 99%
“…All therapeutic options remind on the importance of appropriately balancing quality of life with burden and benefits of therapies [ 55 62 , 63 •]. While some studies claim for a common definition for elderly [ 15 , 40 , 57 , 58 ] or describe and evaluate different treatment patterns retrospectively [ 42 , 59 , 60 ] or by pattern analysis [ 48 •, 57 ], some base their treatment recommendations on scoring age, KPS, and co-morbidity [ 55 , 57 ]. Most studies acknowledge the inherent diversity of elderly patients with its diversity between calendar age and biological age [ 60 – 62 , 63 •] while a few of them recommend the use of geriatric assessment to guide treatment assignment for elderly patients with GBM [ 56 , 60 , 63 ].…”
Section: Future Directionsmentioning
confidence: 99%